Interventions for Stigma Reduction – Part 1: Theoretical Considerations - Silatham Sermrittirong; Ajit Dalal; Miriam Heijnders; Hugh Alistair Cross; Stephanie Mak (Disability, CBR and Inclusive Development)
The contributors to the Working Group that produced this paper are like countless others who are confronted by programme realities in developing countries, such as the pressure to respond to the challenge of stigma in environments of extreme poverty, the issues of scant resources and the requirements to adapt objectives accordingly, and the competing demands for relief and emergency aid. It is in such contexts that researchers have the responsibility of making evidence-based recommendations and yet, regarding stigma interventions, they are confronted by a domain almost devoid of reliable evidence. Without examples of comparable situations that can be reviewed, it may be possible to make progress only through recourse to theoretical concepts. Broad guidelines, based on respected theories, may prove to be a sound foundation on which intervention programmes can be designed.   In this article, the discrete components of stigma that should be targeted in stigma intervention programmes are identified. It is also recommended that since stigma affects different levels in society simultaneously, stigma programmes should be multi-targeted and designed with an intention to adjust interactions between groups at different societal levels.   This article lays the foundation for a companion article that presents a generally applicable method by which plans for stigma interventions can be assessed (Interventions for Stigma Reduction – Part 2: Practical Applications).   DOI: 10.5463/dcid.v22i3.70